Glycopeptide antibiotic analogs for selective inactivation and two-photon imaging of vancomycin-resistant strains. Issue 25 (8th March 2016) - Ariyasu, Shinya; Too, Pei Chui; Mu, Jing; Goh, Chi Ching; Ding, Yichen; Tnay, Ya Lin; Yeow, Edwin Kok Lee; Yang, Liang; Ng, Lai Guan; Chiba, Shunsuke; Xing, Bengang
Abstract : Theranostic divalent vancomycin systems exhibit selective antibacterial activity against vancomycin-resistant strains and can be applied for two-photon fluorescence imaging. Abstract : A novel theranostic divalent vancomycin analog using a planar 1, 8-diazapyrene moiety as a rigid scaffold exhibits potent and selective antibacterial activity against Gram (+) bacteria including vancomycin-resistant strains, while having minimal influence on Gram (−) bacteria and mammalian cells. Moreover, this theranostic analog can be also applied for selective two-photon fluorescence imaging of Gram (+) bacteria.